2016
DOI: 10.1088/1748-9326/11/11/114027
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing investments in national-scale forest landscape restoration in Uganda to maximize multiple benefits

Abstract: Forest loss and degradation globally has resulted in declines in multiple ecosystem services and reduced habitat for biodiversity. Forest landscape restoration offers an opportunity to mitigate these losses, conserve biodiversity, and improve human well-being. As part of the Bonn Challenge, a global effort to restore 350 million hectares of deforested and degraded land by 2030, over 30 countries have recently made commitments to national forest landscape restoration. In order to achieve these goals, decision-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 27 publications
2
35
0
Order By: Relevance
“…Outputs from the multi-objective genetic algorithm were used to analyze tradeoffs between P reductions and costs. Such multi-objective spatial optimization approaches are common when solving conservation problems at regional scales (Kennedy et al 2016, Gourevitch et al 2016). We implemented the genetic algorithm using the Distributed Evolutionary Algorithms in Python package in Python version 2.7 (Fortin et al 2012).…”
Section: Genetic Algorithm Optimizationmentioning
confidence: 99%
“…Outputs from the multi-objective genetic algorithm were used to analyze tradeoffs between P reductions and costs. Such multi-objective spatial optimization approaches are common when solving conservation problems at regional scales (Kennedy et al 2016, Gourevitch et al 2016). We implemented the genetic algorithm using the Distributed Evolutionary Algorithms in Python package in Python version 2.7 (Fortin et al 2012).…”
Section: Genetic Algorithm Optimizationmentioning
confidence: 99%
“…Efficiency frontiers were modeled in Uganda as part of a multi-criteria spatial optimization study for systematic restoration planning (Gourevitch et al 2016). Different regions of the country vary in their potential for improving the supply of specific ecosystem services and biodiversity.…”
Section: Tools For Modeling Synergies and Trade-offs Between Ecosystementioning
confidence: 99%
“…This result is explained by the fact that conditions where water quality is improved most differ from those where carbon storage is maximized. Water quality is improved most in areas close to stream networks that have steep slopes and large upslope watershed areas, whereas increase in carbon storage is highest in severely degraded areas with relatively high mean temperatures and annual precipitation and lower seasonality (Gourevitch et al 2016). Efficiency frontiers with other combinations of objectives, such as carbon storage and biodiversity, water quality and biodiversity, or avoided opportunity costs and carbon storage showed that regardless of where restoration is implemented, carbon storage, water quality and biodiversity will be improved.…”
Section: Tools For Modeling Synergies and Trade-offs Between Ecosystementioning
confidence: 99%
See 2 more Smart Citations